1988
DOI: 10.1111/j.1600-0447.1988.tb05146.x
|View full text |Cite
|
Sign up to set email alerts
|

Attempted suicide by jumping: Clinical and social features

Abstract: A group of 46 persons who had attempted suicide by jumping was compared on clinical and social-demographic parameters with another group of 214 persons who had attempted suicide by drug overdose. The differential characteristics of persons attempting suicide by jumping are the following: more often men, of a more advanced age, married or widowed, more often suffering from major psychopathology (that is affective psychosis-depressive type or schizophrenia), and quite frequently having a serious somatic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
10
1
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
6
10
1
1
Order By: Relevance
“…In a study examining 22 recorded attempted suicides by jumping, 21 were linked to psychiatric illness. 12 This ®nding is corroborated by Kontaxakis et al 13 who identi®ed that of a sample of individuals who attempted suicide by jumping, 72% demonstrated either`aective psychosis-depressive type' or`schizophrenic psychosis'. Certainly jumping is an extremely violent means of suicide, and it has been suggested that individuals using it should be considered as having high suicidal intention.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…In a study examining 22 recorded attempted suicides by jumping, 21 were linked to psychiatric illness. 12 This ®nding is corroborated by Kontaxakis et al 13 who identi®ed that of a sample of individuals who attempted suicide by jumping, 72% demonstrated either`aective psychosis-depressive type' or`schizophrenic psychosis'. Certainly jumping is an extremely violent means of suicide, and it has been suggested that individuals using it should be considered as having high suicidal intention.…”
Section: Introductionsupporting
confidence: 71%
“…18 One possible explanation for the higher representation of people in this study who have schizophrenia concerns the method of attempted suicide, whereby individuals who have schizophrenia are over represented in a population of people who`j ump or fall'. 13 Within this sample, 85% of people had sustained a spinal cord injury as a result of deceleration. However, whilst psychiatric diagnoses were made for 81% (n=111) of the sample, these diagnoses were identi®ed in reports and case notes dating between 1951 and 1992.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Les données de la littérature regroupant l'ensemble des cas de précipitation mentionnent en général une prédominance de patients présentant des psychopathologies sévères (schizophrénie, maladie dépressive majeure) [8][9][10][11]. Cependant, certains auteurs n'ont trouvé aucune différence entre les groupes de suicidants quant à leur psychopathologie [12].…”
Section: Discussion Epidémiologieunclassified